IllustrisTNG in the HSC-SSP: No Shortage of Thin Disk Galaxies in TNG50 - Dewang Xu; Hua Gao; Connor Bottrell; Hassen M. Yesuf; Jingjing Shi (The Astrophysical Journal, 2024)
We perform a thorough analysis of the projected shapes of nearby galaxies in both observations and cosmological simulations. We implement a forward-modeling approach to overcome the limitations in previous studies, which hinder accurate comparisons between observations and simulations. We measure axis ratios of z = 0 (snapshot 99) TNG50 galaxies from their synthetic Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP) images and compare them with those obtained from real HSC-SSP images of a matched galaxy sample. Remarkably, the comparison shows excellent agreement between the observations and the TNG50 simulation, challenging previous claims that ΛCDM models underproduced the abundance of thin galaxies. Specifically, for galaxies with stellar masses $10\leqslant log(M_{\star }/M_{\odot })\leqslant 11.5$ , we find ≲0.1 σ tensions between the observations and the simulation, a stark contrast to the previously reported ≳10 σ tensions. We reveal that low-mass galaxies $(M_{\star }\lesssim {10}^{9.5}\,M_{\odot })$ in TNG50 are thicker than their observed counterparts in HSC-SSP and attribute this to the spurious dynamical heating effects that artificially puff up galaxies. We also find that, despite the overall broad agreement, TNG50 galaxies are more concentrated than the HSC-SSP ones at the low- and high-mass end of the stellar mass range of $9.0\leqslant log(M_{\star }/M_{\odot })\leqslant 11.2$ and are less concentrated at intermediate stellar masses. But we argue that the higher concentrations of the low-mass TNG50 galaxies are not likely the cause of their thicker/rounder appearances. Our study underscores the critical importance of conducting mock observations of simulations and applying consistent measurement methodologies to facilitate proper comparison with observations.